Analisis Kinerja Kepala Sub Bagian Umum Dalam Kepengawasan Kegiatan Administrasi Di Badan Pengelola Keuangan Dan Aset Kabupaten Deli Serdang - Halawa, Fahuwusa; Ritonga, Syafruddin; Angelia, Nina (Universitas Medan Area, 2024)
The background of the problem in this thesis is the prablem of oversight of incoming and outgoing mail at the financial and Asset Management Agency of Deli Serdang Regency. To find out the factors how the managementof incoming and outgoing letters at the financial and Asset Management Agency of Deli Serdang Regency. This study uses qualitative methods as data analysis. Sources of data in this study were the Head of the General Subdivision collection techniques, namely observation, interviws and documentation. Manegement of incoming and outgoing mail at the Deli Serdang Regency Financial and Asset Management Agency is prioritized to be more thorough in checking about letters, date of letters, scheduling letters, and where the leters are sent. The Management of incoming and outgoing mail at the Financial and Asset Management Agency of Deli Serdang Regency is an increasing workload in carrying out tasks by each agency secretary and Civil service civi Affairs.